Two new species of Jasminum (Oleaceae) from Peninsular Thailand - Kiew, Ruth (Thai Forest Bulletin (Botany), 2017)
Two new species from the Peninsular Region of Thailand, Jasminum peninsulare Kiew from Ranong, Phangnga, and Pattani Provinces and J. ranongense Kiew from Ranong Province, are described and illustrated. Previously, they had both been confused with J. kedahense (King & Gamble) Ridl. from Malaysia and included under this name in the Flora of Thailand.